Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Cerita Program Linear - Yolanda Putri, Riska; Kartika Sari, Raras (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze the mistakes of Mathematics Education Study Program 2021 A (PM21A) students in solving linear program story problems. The research method used is descriptive qualitative. The instruments used in this research are an interview sheet, a field survey sheet and two linear program story questions that will be given to students. The subjects of this research were five students and the subjects were determined using random sampling techniques. The collected data is analyzed in depth to identify common errors that arise in the understanding and application of linear programming concepts. Based on the analysis of errors in student answers, several types of errors were found, including: 1) Lack of order and detail in the completion steps. 2) Implementation errors at the final stage. 3) Difficulty understanding the questions and the formula for the solution steps. 4) Error in the substitution step. 5) Lack of detailed explanations. The results of this research contribute to the understanding of student errors in solving linear programming story problems. Implementing learning recommendations can help minimize these errors and improve students' understanding and skills in learning linear programming concepts